MALL OTOMOTIF DI GORONTALO DENGAN TEMA ARSITEKTUR HIGH TECH DI GORONTALO - Meikel Rahim; Muh. Rijal Syukri; Elvie F. Mokodongan (JAMBURA Journal of Architecture, 2023)
ABTRACT.The complexity of Gorontalo province in terms of social, economic, and infrastructure has increased in motor vehicle numbers. The automotive industry has experienced rapid growth in line with the modernization of the era. This is evident from data by the Statistics Indonesia of Gorontalo province, which shows an annual increase in the number of motor vehicles in the region. Hence, there is a need for an Automotive Mall, a centralized building that caters to all consumer needs in the automotive industry. The problem formulation for designing the Automotive Mall in Gorontalo is how to design the Automotive Mall in Gorontalo and how to implement the high-tech architectural theme in the said design. The objective of designing the Automotive Mall in Gorontalo is to create a high-tech architectural design for the Automotive Mall in Gorontalo. This study applied the descriptive method by collecting primary and secondary data sources and explaining and analyzing them as a description. Data were obtained from a literature review, object observation, comparative study, and interviews with relevant stakeholders.High-tech architecture is an architectural style that combines elements from the technology industry with emerging technologies into a building design. The result obtained is the design of an Automotive Mall in Gorontalo with a High-tech architectural theme characterized by transparent materials and vibrant, evenly distributed colors. The application of High-tech architecture is expected to bring distinct characteristics to the Automotive Mall in Gorontalo.ABSTAK.Seiring dengan semakin kompleksnya pembangunan provinsi Gorontalo dari segi pembangunan sosial, ekonomi dan infrastruktur, hal ini mempengaruhi jumlah kendaraan bermotor. Perkembangan industri otomotif semakin pesat seiring dengan perkembangan zaman yang semakin modern, hal ini dapat dilihat dari data berdasarkan data BPS provinsi Gorontalo dimana setiap tahunnya jumlah kendaraan bermotor meningkat di provinsi Gorontalo. Sehingga dibutuhkan suatu kegiatan perniagaan otomotif yang teratur dan terkonsentrasi dalam satu Gedung yang menawarkan semua kebutuhan konsumen di bidang otomotif yaitu Mall Otomotif.  Rumusan masalah dari perancangan Mall Otomotif Gorontalo ini adalah bagaimana mendesain Mall Otomotif di Gorontalo, serta baagaimana penerapan tema arsitektur high tech pada perancangan Mall Otomotif di Gorontalo. Tujuan rancangan Mall Otomotif di Gorontalo adalah untuk menghasilkan desain Mall Otomotif di Gorontalo yang menerapkan Arsitektur High Tech. Penelitian ini menggunakan metode deskriptif dengan pengumpulan sumber data primer dan sekunder kemudian dijelaskan dan dianalisa dalam bentuk uraian. Data-data yang diperoleh dengan cara studi literatur, observasi objek, studi komperasi serta melakukan wawancara dengan pihak terkait. Arsitektur High Tech adalah sebuah gaya arsitektur yang menggabungkan elemen-elemen dari industri teknologi dengan teknologi yang sedang berkembang ke dalam suatu desain bangunan. Hasil yang diperoleh, yaitu desain Mall Otomotif di Gorontalo dengan Tema Arsitektur High Tech.  Pengunaan material yang transparan, dan pewarnaan yang cerah dan merata merupakan karakteristik dari tema arsitektur High Tech yang diterapkan pada Mall Otomotif di Gorontalo. Penggunaan arsitektur High Tech diharapkan menghadirkan ciri yang khas untuk Mall Otomotif di Gorontalo.